Biosorption of lead using Bacillus badius AK strain isolated from compost of green waste (water hyacinth). Issue 13 (18th July 2017) - Vishan, Isha; Sivaprakasam, Senthilkumar; Kalamdhad, Ajay
ABSTRACT: The bacterial strain Bacillus badius AK isolated from water hyacinth compost was investigated for biosorption characteristics in Pb(II) removal. Batch mode experiments depicted the optimum conditions for biosorption as pH at 4, the temperature of 30°C, 150 rpm of the rotational speed at biomass concentration of 20 mL with 1.7 × 10 16  colony forming unit per milliliter (CFU/mL) value, at 100–150 mg/L concentration of Pb(II). The bacterial biomass was used in its native and non-pretreated state, unlike the dried, freeze-dried or chemically treated biomass. The biosorption followed pseudo-second-order kinetics and isotherm fitted well to the Langmuir model. Maximum Pb(II) biosorption was observed at 1.7 × 10 16  CFU/mL. Influence of Pb(II) on the growth of bacterial biomass was examined by fitting the monod's model. Specific growth rate and maximum specific growth rate of B. badius AK was observed as 0.05 and 2.54 h −1, respectively; biomass yield coefficient was 11.81. The results indicated that bacterial biomass was efficient, robust and cheaper biosorbent for removal of Pb(II). GRAPHICAL ABSTRACT: